Character of Diction of Headline News in West Sumatra Mass Media - Elly Delfia (Masyarakat Linguistik Indonesia Universitas Andalas, 2017)
Diction headline mass media is important because it describes the overall news content. The mass media has a moral responsibility to provide learning for the reader about the correct use of language. That's called character diction. Diction character or character choice of words used in the title of the news media can influence the character speaking readers for diction has meaning and soul. Diction used in the mass media headlines West Sumatra, including euphimisme, sarcasm, regional language (language Minangkabau), foreign language (English), idioms, abbreviations and acronyms, Indonesian non standard, and nicknames